Title in English ( Contribution of physical and sports recreational activities in the fight against the scourge of drugs among young people - حويش علي,; عزوز محمد, (sports creativity, 2025)
This study aimed to know the extent of the contribution of physical and sports activities in the fight against the scourge of drugs among the youth, and through what we have noticed about the lack of awareness of the importance of physical sports and recreational activities in creating psychological and social balance, the researcher has used the descriptive method on a sample of 05 young people were communicated The questionnaire and interview were used as tools in his research. Through the results of the study, the researcher concluded that the physical and sporting activities are an effective contribution to the fight against the drug scourge among the youth. Recreational facilities of the causes of the outbreak of the drug scourge